The Influence of Financial and Macroeconomic - Raden Roro Anita Nur Rimadhani; Noer Azam Achsani; Hendro Sasongko (Universitas Tidar, 2023)
The feed industry plays an important role in the economy, as well as in stock investment activities. The performance of feedstock companies is highly dependent on internal and external conditions. This condition becomes an interesting thing to study related to the effect of stock returns. The method used in this study is panel data regression, with data samples from 4 companies with a quarterly period from 2017 to 2021. The quantitative approach uses an econometric approach to determine the financial and macroeconomic performance factors on stock prices in the animal feed sub-sector. The financial performance variables used are Cash Ratio (CashR), Debt Equity Ratio (DER), Net Profit Margin (NPM), Inventory Turnover (ITO), and macroeconomic variables, namely the rupiah exchange rate against the US dollar (exchange rate), international soybean prices, the price of local corn. The results show that the ratio of profitability, liquidity, solvency, and exchange rates is an important part that must be considered before investing in a feed company. Industry NPM performance is 3 percent, where the company with the highest NPM is CPIN and the lowest is SIPD. The industry average CashR performance is 0.24, with the highest CashR company CPIN and the lowest MAIN. The industry's ITO performance is 4.06 times, with the company's highest ITO ratio being CPIN and the lowest being JPFA. The industry DER value is 1.10, with the highest DER company CPIN and three other companies (JPFA, MAIN, SIPD) below average.